No evidence of asymptomatic variant CJD infection in immunodeficiency patients treated with UK‐sourced immunoglobulin. Issue 3 (3rd November 2015) - Helbert, M. R.; Bangs, C.; Bishop, M.; Molesworth, A.; Ironside, J.
Abstract : Surveillance of 75 immunodeficiency patients exposed to UK‐sourced immunoglobulin, including batches derived from donors who went on to develop vCJD, has not detected any clinical cases of vCJD, or of asymptomatic infection in 15 patients with available tissue samples of sufficient quality for testing.